The mountain's gift - Guan, Yang Sheng (2016)
The Mountain’s Gift is a graphic novel project in a fictional, Low-science fantasy setting. It is the beginning of what is hopefully a longer term series of future work that seeks to progressively build up this fictional world through conflict, adventure and immersion. In addition to the staple elements of the fantastic, The Mountain’s Gift conveys more subtle themes such as innocence, ignorance and coming of age, countering the darker, grim visuals with the protagonist’s naiveté.